Engineering of cell membrane to enhance heterologous production of hyaluronic acid in Bacillus subtilis. Issue 1 (23rd October 2017) - Westbrook, Adam W.; Ren, Xiang; Moo‐Young, Murray; Chou, C. Perry
Abstract: Hyaluronic acid (HA) is a high‐value biopolymer used in the biomedical, pharmaceutical, cosmetic, and food industries. Current methods of HA production, including extraction from animal sources and streptococcal cultivations, are associated with high costs and health risks. Accordingly, the development of bioprocesses for HA production centered on robust "Generally Recognized as Safe (GRAS)" organisms such as Bacillus subtilis is highly attractive. Here, we report the development of novel strains of B. subtilis in which the membrane cardiolipin (CL) content and distribution has been engineered to enhance the functional expression of heterologously expressed hyaluronan synthase (HAS) of Streptococcus equisimilis (SeHAS), in turn, improving the culture performance for HA production. Elevation of membrane CL levels via overexpressing components involved in the CL biosynthesis pathway, and redistribution of CL along the lateral membrane via repression of the cell division initiator protein FtsZ resulted in increases to the HA titer of up to 204% and peak molecular weight of up to 2.2 MDa. Moreover, removal of phosphatidylethanolamine and neutral glycolipids from the membrane of HA‐producing B. subtilis via inactivation of pssA and ugtP, respectively, has suggested the lipid dependence for functional expression of SeHAS. Our study demonstrates successful application of membrane engineering strategies to develop an effective platform for biomanufacturing of HA with B. subtilis strains expressing Class I streptococcal HAS. Abstract : Bacillus subtilis is an ideal bacterium for biomanufacturing, and has been applied successfully to heterologous hyaluronic acid (HA) production on an industrial scale. Modulating the cardiolipin content and distribution in cell membrane can significantly enhance both the molecular weight and titer of HA produced in B. subtilis expressing streptococcal hyaluronan synthase.